Strategi Manajerial Kepala Sekolah dalam Pengembangan Fasilitas Sarana dan Prasarana di SMP Swasta Nurul Khoir Kota Jambi - Ayu Arfika Sari; Riftiyanti Savitri (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to analyze the principal’s strategies in improving educational facilities and infrastructure at Nurul Khoir Private Junior High School in Jambi City. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and educational staff. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the school’s facilities and infrastructure are still limited, particularly in learning-support facilities such as laboratories, sports fields, and parking areas. The main constraints faced by the school include limited financial resources and inadequate availability of educational facilities. The principal’s strategies to address these challenges include priority-based planning, stakeholder involvement in management processes, and optimization of existing facilities. This study concludes that the principal’s leadership plays a crucial role in the effective management and development of educational facilities and infrastructure, especially in private schools with limited resources.